Assessing Customer Satisfaction Improvement in the Sport Physiotherapy Industry in Penang, Malaysia - Chee, Soon Liang (2023)
The dissertation aims to look at the elements that influence client loyalty to sports physiotherapy service providers throughout Penang, Malaysia. A mixed research strategy, integrating qualitative and quantitative methodologies, was used. The Expectancy Value Model (EVM) led to the study's aims, which attempted to discover the factors of customer loyalty among athletes needing sports injury rehabilitation treatments. The study design included a detailed review of peer-reviewed literature to identify evidence-based determinants influencing customer satisfaction. A self- administered questionnaire was utilized to get data from 101 athletes on characteristics like familiarity with the service provider (FAM), trust (TRST), satisfaction (SAT), as well as attitudinal loyalty (AL), all of which contribute to customer loyalty (CL). The acquired data was subjected to evaluations of central tendency, correlational analysis, and hypothesis testing. According to the findings, trust, contentment, and attitudinal loyalty all positively and substantially influenced consumer loyalty. However, familiarity did not. Trust appeared as a critical component, stressing its importance in establishing and maintaining consumer loyalty. Satisfaction and attitudinal loyalty were critical, emphasizing the importance of individualized and high-quality services in fostering loyalty. The research summary showed the need to take a comprehensive strategy to encourage customer loyalty by concentrating on trustworthiness, athlete happiness, and delivering great emotional experiences. The study's impact size, measured by an R-squared value of 0.419, revealed that the combined influence of the factors made up 41.9% of the variance within customer loyalty. This investigation adds to the sports physiotherapy knowledge by presenting a novel model for analyzing customer loyalty in Penang, Malaysia, also to recommending possibilities for future studies and consequences for industry stakeholders.